2009
DOI: 10.1017/s0029665109991807
|View full text |Cite
|
Sign up to set email alerts
|

Symposium on ‘Geographical and geological influences on nutrition’ Factors controlling the distribution of selenium in the environment and their impact on health and nutrition

Abstract: Se is essential to human and animal health but can be toxic in excess. An interest in its geochemistry has developed alongside a greater understanding of its function in a number of health conditions. Geology exerts a strong control on the Se status of the surface environment; low-Se rock-types (0·05–0·09 mg Se/kg) make up the majority of rocks occurring at the Earth's surface, which in turn account for the generally low levels of Se in most soils. However, there are exceptions such as associations with sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 56 publications
2
139
0
4
Order By: Relevance
“…16,17 These differences may reflect the considerable depletion of selenium in soil observed in parts of Europe but not throughout North America. 18 We may have prescribed an insufficient dose of selenium or used an ineffective dosing schedule, since a higher-thannormal level of selenium in the blood may be associated with the best outcome 19 and an initial bolus of selenium might have been more effective than the continuous administration we used. 20 The strengths of this study include the randomized and blinded design, rigorous determination and adjudication of infection, and intention-to-treat analysis, all of which augment the internal validity of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 These differences may reflect the considerable depletion of selenium in soil observed in parts of Europe but not throughout North America. 18 We may have prescribed an insufficient dose of selenium or used an ineffective dosing schedule, since a higher-thannormal level of selenium in the blood may be associated with the best outcome 19 and an initial bolus of selenium might have been more effective than the continuous administration we used. 20 The strengths of this study include the randomized and blinded design, rigorous determination and adjudication of infection, and intention-to-treat analysis, all of which augment the internal validity of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Global Se intakes (in µg day −1 ) show significant changes among various countries, whereas the average intakes are usually low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), temperate , and sufficient (85-150) in parts of China, North America, and Europe respectively (FAO/WHO, 1998; WHO, 2011). In more details, it is found that daily dietary Se intake ranges from 7 to 4.990 µg, with mean values of 40 µg in Europe and 93 to 134 µg for women and men in the USA respectively (Rayman, 2012).…”
Section: Selenium In the Soil-plant-food Systemsmentioning
confidence: 99%
“…In animals, clinical signs of Sedeficiency include reduced appetite/growth/fertility and muscle weakness; generally described as white muscle disease (WMD) (Levander, 1986). In most cases, food forms the main source of Se for humans because concentrations in water and air are generally low (WHO, 1987;Fordyce, 2005;Fordyce, 2007;Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and acid-neutral soils are typical as in much of Northern Europe (Fordyce, 2005;Broadley et al, 2006;Johnson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%